Frozen elephant trunk procedure for extensive pneumococcal thoracic aortitis. (February 2017) - Guihaire, Julien; Revest, Matthieu; Heautot, Jean-François; Verhoye, Jean-Philippe
Infectious arteritis is an insidious condition commonly associated with a long diagnostic delay. We report the management of extensive pneumococcal thoracic aortitis in a 64-year-old woman. The frozen elephant trunk procedure was performed to repair the aortic arch. Prolonged aortic wall cultures were positive for Streptococcus pneumoniae. Late follow-up imaging at 36 months demonstrated no sign of recurrence around the hybrid vascular graft in the thoracic aorta.